Knowledge of health risks, safety practices, acute pesticide poisoning, and associated factors among farmers in rural irrigation areas of northeastern Ethiopia - Keleb, Awoke; Ademas, Ayechew; Abebe, Masresha; Berihun, Gete; Desye, Belay; Bezie, Anmut Endalkachew (Frontiers in Public Health, 2024)
BackgroundPesticide exposure is a major public health issue among farmers affecting make it their health, economic stability, and agricultural productivity. This study aimed to investigate the magnitude and determinants of farmers’ knowledge of health risks, safety practices, and acute pesticide poisoning in the South Wollo Zone, Ethiopia.MethodsA community-based cross-sectional study was conducted in the South Wollo Zone’s irrigation areas from July to August 2022. Using a multistage sampling technique, five out of ten irrigation districts were randomly selected, and three kebeles (the smallest administrative unit) from each district (15 total) were chosen based on intensive irrigation activities. A proportional sample size was allocated across the selected kebeles according to the number of farmers. Trained data collectors conducted face-to-face interviews using a pretested structured questionnaire. Crude and adjusted odds ratios with 95% confidence intervals at a p-value of 0.05 identified statistically significant factors.ResultThe study found that 55.2% of farmers had below mean knowledge of health risks, 63.7% practiced below mean safety practices, and 47.9% experienced acute pesticide poisoning. Significant factors for below mean knowledge included no formal education (AOR = 2.32; 95% CI: 1.27–4.23) and lack of pesticide training (AOR = 2.07; 95% CI: 1.33–3.21). Below mean safety practices were associated with age > 47 years (AOR = 2.07; 95% CI: 1.06–4.04), below mean retailer actions (AOR = 1.97; 95% CI: 1.34–2.89), and below mean attitude (AOR = 1.79; 95% CI: 1.23–2.62). Acute pesticide poisoning was significantly associated with over 10 years of exposure (AOR = 4.34; 95% CI: 2.55–7.39), below mean knowledge (AOR = 2.17; 95% CI: 1.23–2.62), lack of training (AOR = 3.73; 95% CI: 2.33–5.98), and below mean safety practices (AOR = 4.40; 95% CI: 2.86–6.78).ConclusionFarmers’ knowledge of health risks and safety practices was not satisfactory. Low educational status, lack of training, and minimal government involvement were associated with below mean knowledge. Below mean knowledge and below mean safety practices, low education, lack of training, and minimal government involvement were associated with acute pesticide poisoning. Young farmers, limited retailer involvement, and below mean attitudes contribute to unsafe practices.